Single nucleus and spatial transcriptomic profiling of healthy human hamstring tendon - Mimpen, JY; Ramos‐Mucci, L; Paul, C; Kurjan, A; Hulley, PA; Ikwuanusi, CT; Cohen, CJ; Gwilym, SE; Baldwin, MJ; Cribbs, AP; Snelling, SJB (Wiley, 2024)
The molecular and cellular basis of health in human tendons remains poorly understood. Among human tendons, hamstring tendon has markedly low pathology and can provide a prototypic healthy tendon reference. The aim of this study was to determine the transcriptomes and location of all cell types in healthy hamstring tendon. Using single nucleus RNA sequencing, we profiled the transcriptomes of 10 533 nuclei from four healthy donors and identified 12 distinct cell types. We confirmed the presence of two fibroblast cell types, endothelial cells, mural cells, and immune cells, and identified cell types previously unreported in tendons, including different skeletal muscle cell types, satellite cells, adipocytes, and undefined nervous system cells. The location of these cell types within tendon was defined using spatial transcriptomics and imaging, and potential transcriptional networks and cell–cell interactions were analyzed. We demonstrate that fibroblasts have the highest number of potential cell–cell interactions in our dataset, are present throughout the tendon, and play an important role in the production and organization of extracellular matrix, thus confirming their role as key regulators of hamstring tendon homeostasis. Overall, our findings underscore the complexity of the cellular networks that underpin healthy human tendon function and the central role of fibroblasts as key regulators of hamstring tendon tissue homeostasis.